2017
DOI: 10.1371/journal.pone.0172973
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue is the first colonization site of Leptospira interrogans in subcutaneously infected hamsters

Abstract: Leptospirosis is one of the most widespread zoonoses in the world, and its most severe form in humans, “Weil’s disease,” may lead to jaundice, hemorrhage, renal failure, pulmonary hemorrhage syndrome, and sometimes,fatal multiple organ failure. Although the mechanisms underlying jaundice in leptospirosis have been gradually unraveled, the pathophysiology and distribution of leptospires during the early stage of infection are not well understood. Therefore, we investigated the hamster leptospirosis model, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(49 reference statements)
0
10
0
1
Order By: Relevance
“…Recently, the Yoshida group used a hamster model of intradermal inoculation to track post-mortem, after laparotomy, the Murray's LuxCDABE-luminescent L. interrogans. Of great interest, they showed that leptospires first disseminate in the subcutaneous adipose tissue before disseminating in the blood and colonizing the organs including the kidneys [45]. Eye drop inoculation is an interesting route of infection since it mimics a natural route of infection and is considered more physiological than intraperitoneal infection, which bypasses the natural defenses of the skin and mucosa.…”
Section: How L Interrogans Establish Renal Chronicity?mentioning
confidence: 99%
“…Recently, the Yoshida group used a hamster model of intradermal inoculation to track post-mortem, after laparotomy, the Murray's LuxCDABE-luminescent L. interrogans. Of great interest, they showed that leptospires first disseminate in the subcutaneous adipose tissue before disseminating in the blood and colonizing the organs including the kidneys [45]. Eye drop inoculation is an interesting route of infection since it mimics a natural route of infection and is considered more physiological than intraperitoneal infection, which bypasses the natural defenses of the skin and mucosa.…”
Section: How L Interrogans Establish Renal Chronicity?mentioning
confidence: 99%
“…Furthermore, pathogenic, but not saprophytic, Leptospira have been shown to interrupt cell-to-cell junctions in vitro (Sato & Coburn, 2017). Enhanced vascular permeability facilitated by LIC10831 may allow the bacterium to escape host blood vessels to take up residence in preferred host tissues (Barnett et al, 1999;Ozuru et al, 2017).…”
Section: Lic10831 Also Binds Human Ve-cadherinmentioning
confidence: 99%
“…In each of these cases, 69 regulation of pathogenic gene expression was examined in a surrogate host because a plasmid 70 able to replicate in L. interrogans was not available. Promoter fusions to gfp or luciferase genes 71 have been introduced into L interrogans by transposition (21)(22)(23). However, mutational analysis 72 of promoters fused to the reporter is not possible with the transposon-based system; random 73 insertion of the transposon carrying the fusion complicates interpretation of expression levels 74 because the location of the transposon in the chromosome may influence fusion expression.…”
Section: Introduction 29mentioning
confidence: 99%